Price discovery, price behaviour, and efficiency of selected grain commodities traded on the agricultural products division of the JSE securities exchange - Viljoen, Christo (Rhodes University, Faculty of Commerce, Department of Economics, 2004)
Agricultural commodity derivatives were first introduced in South Africa in 1996 after the deregulation of the former marketing system. In the context of its proposed functions, namely price discovery and risk management, the question arose as to whether the futures market developed over time to performed its role efficiently. According to the Efficient Markets Hypo
Keywords: Johannesburg Stock Exchange; Stock exchanges -- South Africa; International economic relations; Primary commodities -- South Africa; Grain trade -- South Africa; Financial futures -- South Africa; Price regulation -- South Africa